Resveratrol attenuates L-DOPA-induced hydrogen peroxide toxicity in neuronal cells - Peritore, Carina S. (Neuroreport, 2012)
A variety of polyphenol antioxidant compounds derived from natural products have demonstrated neuroprotective activity against neuronal cell death. The objective of this study was to investigate the effect of resveratrol (RESV) and bioflavonoids in attenuating hydrogen peroxide (H(2)O(2))-induced oxidative stress in neuronal cells. H(2)O(2) levels were increased by the addition of L-3,4-dihydroxyphenylalanine (L-DOPA) to cultured dopaminergic SKNSH cells. H(2)O(2) was monitored by peroxyfluor-1, a selective H(2)O(2) optical probe. To examine the neuroprotective effects of RESV and bioflavonoids against L-DOPA, we cotreated RESV, quercetin, or (−) epigallocatechin gallate with L-DOPA and monitored for H(2)O(2) levels. The combination of RESV and L-DOPA was 50% more effective at reducing H(2)O(2) levels than the combination of quercetin or epigallocatechin gallate with L-DOPA. However, the combination of each antioxidant with L-DOPA was effective at preserving cell viability.